Property prediction and crack growth behavior in cold sprayed Cu deposits - Chunjie Huang; Mariia Arseenko; Lv Zhao; Yingchun Xie; Andreas Elsenberg; Wenya Li; Frank Gärtner; Aude Simar; Thomas Klassen (Materials & Design, 2021)
Low ductility of metallic deposits manufactured by cold spraying (CS) impedes potential mechanical performances in industrial applications. Through appropriate annealing treatment, the amount of both, non-bonded interfaces and work hardening promoted dislocations during CS can be significantly reduced. Consequently, the annealed samples exhibit higher strength and fracture strain than the as-deposited ones. Cu was selected as a reliable material for CS. To correlate Cu deposit strength with primary process parameters and material properties, the Cu powder strength was assessed. Crack characterization of Cu deposits was performed by in-situ microscopic observations during tensile testing. The direct observation of crack initiation, growth and final fracture allows revealing failure mechanisms. The in-situ tests allow distinguishing the effects of reduced initial defect sizes due to annealing and improved ductility in the vicinity of initial defects on possible crack growth and part failure. Considering the necessary compromise between strength, uniform elongation, ductility and microhardness, a post-spraying annealing process is desirable for CSed Cu deposits. The identification of macroscopic and micro-mechanical properties attained under respective process parameters and influences of annealing processes therefore allow identifying solutions for improvements of CSed deposits for load-carrying applications, which is a prerequisite for using CS as additive manufacturing technique.